(untitled) (Global Journal of Medical Research, 2023)
Context Opioids use in older adults with cancer is growing as do world population over 60 years of age Objectives This study aimed to evaluate the association between the use of opioids and death in older patients with a cancer diagnosis Methods We performed the analysis in a prospective cohort study with an internal comparison group Statistical modeling considered clinical and laboratory variables The cohort included 747 patients Of these 59 patients were using opioids and they were selected to form the exposed group Of the remaining 688 59 were randomized to compose the group not exposed to opioids